Integrated physiological, transcriptomic, and metabolomic analyses provide new insights into hypoxia tolerance in large yellow croaker (Larimichthys crocea) - Yibo Zhang; Jie Ding; Xuelei Wang; Ran Meng; Songpeng Jia; Xiongfei Wu; Junquan Zhu; XiaoMing Peng; Weiliang Shen (Marine Pollution Bulletin, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Oceanic redox evolution in an early Cambrian intrashelf basin, South China - Yuyue Han; Meng Cheng; Jianbo Chen; Thomas J. Algeo; Bo Ran; Mengchun Cao; Zihu Zhang; Haiyang Wang; Dasheng Zhao; Tao Dong; Feng Wang; Taiping Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

ODC1-associated astrocytic urea cycle dysregulation in age-related memory impairment - Mengna Wu; Shengyao Zhang; Xi Zhao; Bingyu Zhang; Guoran Wan; Jie Gui; Meng Zhang; Baoxue Yang; Dilong Chen; Guoli Li; Qiu Chen; Boyue Huang; et al. (Biogerontology, 2026)

A Porous Zn-Salen-Based Organic Ionic Polymer as a Robust Bifunctional Catalyst for CO2 Fixation via Epoxide Cycloaddition - Guo-Ling Li; Rui-Yao Qin; Meng-Meng Wang; Qing Li; Shijian Lu; Jin-Shui Su; Qi Zhang; Yun Zhao; Ran Zhang; Zhong-Hai Ni (Journal of Environmental Chemical Engineering, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Asymmetric spectral modulation of bioinspired Janus metafabric toward environment-adaptive thermal and moisture management under extreme conditions - Yang Wu; Long Zhang; Hao-Ran Yang; Jiaqi Li; Yuzhen Hou; Chang-Shun Li; Bobo Shi; Meng Zhou; Wulin Shang; Weiqing Kong; Huan Xu; Gang Zhou; et al. (Chemical Engineering Journal, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Integrated crop-livestock systems: Closing nitrogen cycles to improve nitrogen utilization efficiency in sustainable ruminant production - Guangyou Ran; Gonzalo Cantalapiedra-Hijar; Hieu Nguyen-Ba; Guangyong Zhao; Jun Zhang; Meng M. Li (Agriculture, Ecosystems & Environment, 2026)

Uncovering the climate vulnerability of China’s poverty alleviation frontiers - Feng Zhao; Lijun Zuo; Yuyu Zhou; Liangzhi You; Huabing Huang; Rui Sun; Yuanyuan Zhao; Xunhuan Li; Dawei Zhang; Ran Meng (Global Environmental Change, 2026)

Metal-air fuel cells for phosphorus recovery from wastewater: A critical analysis of principles, progress, and application perspectives - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Yuan Liu (Chemical Engineering Journal, 2026)

Trans-cinnamaldehyde alleviates high-fat diet-induced oxidative stress in zebrafish via direct and gut microbial mediated activations of antioxidant pathways - Delong Meng; Xiaoying Zhu; Jingyu Luan; Xingyu Chen; Tsegay Teame; Benjamin Earl Niemann; Chao Ran; Yalin Yang; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Zhigang Zhou (Marine Life Science & Technology, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Source apportionment and health risk prioritization of groundwater contamination in a coal-mining area: An integrated SOM-PMF-Monte Carlo framework - Zheng Yin; Shiqi Zhang; Xiao Fu; Ran Sun; Ran Lv; Meng Yuan; Ziyuan Gao; Gang Wu (Journal of Environmental Management, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

H₂O₂-induced green synthesis of EGCG-flavonoid carrier-free nanoparticles:The role of hydroxyl group number governing formation and function - Qian Zhou; Ran Feng; Chen-Chen Wang; Si-Jie Wu; Qiu-Ya Ji; Ran Meng; Bao Zhang (Food Chemistry, 2026)

Assessment of applicators’ exposure to pesticides during knapsack mist sprayer application in rice fields - Mei Chenghan; Tao Chuanjiang; Zhang Liying; Meng Yuxi; Nie Siqiao; Pu Entang; An Xuehua; Qu Mengmeng; Tao Lingmei; Liu Ran; Huang Lan; Zhang Bingmei (Environmental Toxicology and Pharmacology, 2026)

A novel bigel type featured as O1/W/O2 microstructure achieved by whey protein aggregates as dual-interfaces mediator: Enabling dual functions in low-fat cream cheese simulation and co-delivery of pterostilbene/gallic acid - Qiuya Ji; Kai Ye; Ran Meng; Sijie Wu; Ran Feng; Bao Zhang (Food Chemistry, 2026)

Polysaccharide-based inflammatory microenvironment-responsive nanocarriers for ulcerative colitis: Advances in design, mechanisms, and therapeutic applications - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Carbohydrate Polymers, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Cerebral blood flow alterations in non-auditory tinnitus: implications for cerebral venous congestion pathophysiology - Lu Liu; Milan Jia; Hui Li; Yifan Zhou; Huimin Jiang; Weiyue Zhang; Chenxia Zhou; Jiangang Duan; Ran Meng; Chen Zhou; Xunming Ji (Brain Imaging and Behavior, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Porous MXene nanoplatform with ultrahigh drug loading for synergistic photothermal/photodynamic therapy and drug resistance reversal in osteosarcoma - Zhen Song; Ran-Ran Zhang; Zi-Chao Yan; Jie Wang; Youchang Liu; Chang-Qing Jiang; Meng Qiu; Bing-Xin Zheng; Bin Yue (Chemical Engineering Journal, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Sub-denaturing thermal pretreatment modulates lactoferrin-quercetin interactions: Structural dynamics, binding mechanisms, and functional synergy - Si-Jie Wu; Qi-Bin Kuang; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Food Hydrocolloids, 2026)

Water soluble polysaccharides from the fruits of Lycium barbarum L. improve glucose and lipid metabolism and boost immune function in elderly mice fed a high-fat diet - Wanyi Wang; Haiyu Shi; Meng Zhang; Jia Mi; Lu Lu; Bo Jin; Lutao Zhang; Abdul Rehman; Chunhong Liu; Yamei Yan; Linwu Ran (Food Bioscience, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

Exploring the regulation mechanism of digestibility of starch-polyphenol-protein ternary system by pH from multiple perspectives - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao Zhang (Food Chemistry, 2025)

Comprehensive physiological, transcriptomic, and metabolomic analyses reveal that preservation paper treatment mediates the AsA-GSH cycle and energy metabolism pathways to delay the ageing mechanism of Pleurotus ostreatus - Zhi Yan; Lingshuai Meng; Huaituo Yang; Donglei Zhang; Lulu Ran; Chao Ma (Food Packaging and Shelf Life, 2025)

Nanogel cage based on oxidized sodium alginate sacrificial template: Enhanced stability and protein crosslinking performance of immobilized TGase - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao Zhang (Carbohydrate Polymers, 2025)

Treatment and reuse of hypo-salinity wastewater using a novel starch-based flocculant with ultra salt-sensitive characteristics - Shengxin Wang; Wei Zhao; Heling Guo; Rongjie Wang; Qi Zhang; Meng Gu; Tingting Wei; Tingmin Ran; Ruichao Zhou; Yulin Shi (Carbohydrate Polymers, 2025)

Construction of OSA-starch and caffeic acid composite system driven by high pressure homogenization: Multiscale structural evolution and digestibility regulation mechanism - Ran-Ran Deng; Ran Feng; Ran Meng; Si-Jie Wu; Han Tao; Bao Zhang (Food Chemistry, 2025)

New insights into the regulation mechanism of starch digestibility by polyphenol structures in starch-polyphenol-protein ternary system - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao Zhang (Food Chemistry, 2025)

Mechanism of reducing rice starch digestibility by quinoa protein amyloid-like fibrils pretreated with magnetic field - Ran Meng; Chang-Qing Hong; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Bao Zhang (Food Chemistry, 2025)

FiVOS: A fish segmentation algorithm based on interactive video object segmentation and filter enhancement - Yuqing Duan; Song Zhang; Shili Zhao; Xiaoyi Gu; Yan Meng; Daoliang Li; Ran Zhao (Computers and Electronics in Agriculture, 2025)

Preliminary study on ameliorative effects of P-Hydroxycinnamic acid on high-fat diet-induced injury in zebrafish - Qianyao Kuang; Delong Meng; Zhen Zhang; Xingyu Chen; Tsegay Teame; Hongwei Yang; Yalin Yang; Chao Ran; Yuanyou Li; Zhigang Zhou (Fish & Shellfish Immunology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Potential role of dietary whole grains in Alzheimer's disease: bioactive components, mechanistic insights, and epidemiological evidence - Meng Shen; Xinru Yu; Suyang Wu; Ju Qiu; Ran Wang; Kai Li; Qian Zhang (Trends in Food Science & Technology, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Probabilistic failure mode-based prediction method for flexural design capacities of precast reinforced concrete and prestressed concrete beams - Yukun Hu; Jitao Yao; Kaikai Cheng; Luyang Zhang; Meng Ran; Hao Li; Jiewei Xu (Bulletin of Earthquake Engineering, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

Microglial purinergic signaling in Alzheimer’s disease - Shu-Ya Mei; Ning Zhang; Meng-jing Wang; Pei-ran Lv; Qi Liu (Purinergic Signalling, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

In situ transglutaminase cross-linking mediated protein-stabilized high internal phase emulsion gels to emulate dorsal adipose tissue: The role of continuous phase networks - Liang Guo; Yu-hang Xue; Yi-ran Zhang; Wen-yan Chen; Yao-siyi Yuan; Shen-shen Tian; Yue-Cheng Meng; Jie Chen (Food Chemistry, 2025)

Mechanism of microparticulated whey protein replacing milk fat during the production stages of renneted casein gel - Ran Meng; Ran Feng; Runhao Fu; Zihan Wang; Bao Zhang (Food Hydrocolloids, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Whey protein-structured oleogels: Effect of α-lactalbumin addition and ultrasonication treatment on oleogelation - Qiu-Ya Ji; Ran Feng; Yu-Nong Chen; Chao Zhang; Jiao Wu; Meng-Jie Yu; Bao Zhang (Food Chemistry, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Manganese on P, N self-doped biochar toward promoting periodate activation for highly efficient tetracycline degradation: Performance and mechanisms - Xiaofang Pan; Hong Ma; Rongning Zhang; Ran Deng; Meng Li; Binfei Yang; Ruiying Zhu; Li Zhao; Yong Liu; Xiaobo Gong (Journal of Environmental Chemical Engineering, 2025)

Study on the dissolved inorganic carbon cycling and carbon emission during the wet season across cascade hydropower stations on the Jinsha River, southwestern China - Dan Zhang; Yufei Bao; Jingjie Feng; Yu Xu; Yuchun Wang; Ran Li; Yanliang Du; Zhuo Chen; Shanze Li; Jie Wen; Meng Sun (Gondwana Research, 2025)

Flexible surface acoustic wave technology for enhancing transdermal drug delivery - Jikai Zhang; Duygu Bahar; Hui Ling Ong; Peter Arnold; Meng Zhang; Yunhong Jiang; Ran Tao; Luke Haworth; Xin Yang; Chelsea Brain; Mohammad Rahmati; Hamdi Torun; et al. (Drug Delivery and Translational Research, 2025)
Transdermal drug delivery provides therapeutic benefits over enteric or injection delivery because its transdermal routes provide more consistent concentrations of drug and avoid issues of drugs affecting kidneys and liver functions. Many technologies have been evaluated to enhance drug delivery through the relatively impervious epidermal layer of the skin. However, precise delivery of large hydrophilic molecules is still a great challenge even though microneedles or other energized (such as electrical, thermal, or ultrasonic) patches have been used, which are often difficult to be integrated into small wearable devices. This study developed a flexible surface acoustic wave (SAW) patch platform to facilitate transdermal delivery of macromolecules with fluorescein isothiocyanates up to 2000 kDa. Two surrogates of human skin were used to evaluate SAW based energized devices, i.e., delivering dextran through agarose gels and across stratum corneum of pig skin into the epidermis. Results showed that the 2000 kDa fluorescent molecules have been delivered up to 1.1 mm in agarose gel, and the fluorescent molecules from 4 to 2000 kDa have been delivered up to 100 µm and 25 µm in porcine skin tissue, respectively. Mechanical agitation, localised streaming, and acousto-thermal effect generated on the skin surface were identified as the main mechanisms for promoting drug transdermal transportation, although micro/nanoscale acoustic cavitation induced by SAWs could also have its contribution. SAW enhanced transdermal drug delivery is dependent on the combined effects of wave frequency and intensity, duration of applied acoustic waves, temperature, and drug molecules molecular weights. Graphical Abstract Graphical Abstract: Flexible surface acoustic wave technology for enhancing transdermal drug delivery

Synergistic stabilization of oil-in-water emulsion gels by pea protein isolate and cellulose nanocrystals: Effects of pH and application to 3D printing - Ran Zhu; Jing Zhang; Zong Meng (Food Chemistry, 2025)

Exploring the binding mechanism and functional properties of lactoferrin-berberine complex: Based on multispectral analysis, molecular docking, and dynamics simulations - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Food Chemistry, 2025)

New insights into rice starch-gallic acid-whey protein isolate interactions: Effects of multiscale structural evolution and enzyme activity on starch digestibility - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Carbohydrate Polymers, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

4-Nitrophenol at environmentally relevant concentrations mediates reproductive toxicity in Caenorhabditis elegans via metabolic disorders-induced estrogen signaling pathway - Jia Wang; Jiechen Yin; Danhong Peng; Xiaoqian Zhang; Zhouhong Shi; Weixi Li; Yingchi Shi; Mingjun Sun; Nan Jiang; Beijing Cheng; Xingchen Meng; Ran Liu (Journal of Environmental Sciences, 2025)

Thiolated dextrin nanoparticles for curcumin delivery: Stability, in vitro release, and binding mechanism - Bao Zhang; Shen Long; Ran Feng; Meng-Jie Yu; Bao-Cai Xu; Han Tao (Food Chemistry, 2025)

Functional peptide conjugated ordered gold nanoparticles based rational electrochemical immunosensor for highly stable and selective detection of zearalenone - Qingyue Li; Xiya Zhang; Mengtian Chen; Changwei Luo; Ran Yang; Tong Bu; Meng Dang; Xianqing Huang; Lianjun Song; Pingan Zhang; Liang Liu; Yexuan Mao (Food Chemistry, 2025)

Stabilizing emulsions by ultrasound-treated pea protein isolate - tannic acid complexes: Impact of ultrasonic power and concentration of complexes on emulsion characteristics - Meng-Jie Yu; Ran Feng; Shen Long; Han Tao; Bao Zhang (Food Chemistry, 2025)

Modulating rice digestibility: Mechanisms of ultrasound, oleic acid and moist-heat treatments influence structural, physicochemical and digestive properties - Bao Zhang; Qian Gao; Meng-Jie Yu; Ran Feng; Han Tao (Food Chemistry, 2024)

Novel self-assembled micelles of dual-modified dextrin with pH responsiveness via grafted octenyl succinic anhydride and cysteamine for curcumin delivery - Shen Long; Meng-Jie Yu; Ran Feng; Han Tao; Bao Zhang (Food Chemistry, 2024)

Whipped cream stabilized by faba bean protein isolate microgel particles substituted for sodium caseinate: Whipping performance and foam stabilization analysis - Jing Zhang; Ran Zhu; Zong Meng (Food Hydrocolloids, 2024)

Hollow and heterojunction-structured Janus nanomotors for pyroelectrodynamic and nanozyme-catalyzed tumor therapy - Jie Meng; Wei Wei; Shuang Xie; Junwu Wei; Zhanlin Zhang; Pan Ran; Xiaohong Li (Chemical Engineering Journal, 2024)

Effects of plastic aging on biodegradation of polystyrene by Tenebrio molitor larvae: Insights into gut microbiome and bacterial metabolism - Meng-Qi Ding; Jie Ding; Shan-Shan Yang; Xin-Ran Ren; Shao-Nan Shi; Lu-Yan Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Science of The Total Environment, 2024)

Optimized ammonium-nitrate ratios in constructed wetlands for simultaneously efficient nitrogen removal and greenhouse gas reduction - Ling-Min Zhang; Ran Liu; Xiao-Qin Luo; Ying Liu; Xi-Qi Li; Qing-Jie Meng; Hong-Cheng Wang (Journal of Water Process Engineering, 2024)

Oleic acid treatment of rice grains reduces the starch digestibility: Formation, binding state and fine structure of starch-lipid complexes - Qian Gao; Ran Feng; Meng-Jie Yu; Han Tao; Bao Zhang (Food Chemistry, 2024)

Optimizing entropy weight model to accurately predict variation of pharmaceuticals and personal care products in the estuaries and coasts of the South China - Yuxin Xie; Jieyi Diao; Jing Meng; Jianwen Wang; Jiaer Zhang; Jingru Zhang; Lulu Zhang; Jonathan Y.S. Leung; Ran Bi; Wenhua Liu; Tieyu Wang (Marine Pollution Bulletin, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effects of Tetraselmis subcordiformis (Wille) Butcher with antimicrobial peptides as feed additives on gut microbial community and immunity of turbot (Scophthalmus maximus L.) - Bingkui Zhu; Fengjie Sun; Zhengquan Gao; Ting Yao; Subing Han; Hao Zhang; Yuyang Ma; Yuyong Wu; Ran Du; Chunxiao Meng; Yulin Cui (Journal of Applied Phycology, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Picea pungens exhibits greatest tolerance to short-time thermal stress compared to Picea abies, and Picea omorika - Fangqun Ouyang; Meng Sun; Xia Cui; Mulualem Tigabu; Hui Zhang; Junyu Deng; Junhui Wang; Yu Wei; Ran He (New Forests, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

Dynamic response mechanism and precursor characteristics of gneiss rockburst under different initial burial depths - Dongqiao Liu; Jie Sun; Wen Meng; Manchao He; Chongyuan Zhang; Ran Li; Binghao Cao (Journal of Mountain Science, 2024)

Genomic selection for hypoxia tolerance in large yellow croaker - Jie Ding; Yibo Zhang; Xujie Li; Jiaying Wang; Xinming Gao; Qiumeng Xiang; Zhenyu Gao; Tianyi Lan; Songpeng Jia; Mengqi Lu; Ran Meng; Xuelei Wang; et al. (Aquaculture, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Inactivation of Escherichia Coli by mixed-valent nanoparticles in-situ generated during Fe electrocoagulation - Meng Qiao; Junke Zhang; Ran Mao; Xu Zhao (Water Research, 2023)

Characterization and immune functional analysis of two new type I crustins in the oriental river prawn Macrobrachium nipponense - Hongxia Jiang; Shuaishuai Zhang; Xuewei Liu; Yizheng Li; Huanxin Li; Ran Zhang; Yuhua Li; Meng Zhang; Lei Wang; Miao Yu; Zhigang Qiao; Xuejun Li (Aquaculture, 2023)

Full-scale experimental study and mechanical model for beam-wall joints of prefabricated enclosure structure - Tong Qiu; Xiangsheng Chen; Dong Su; Jiqing Zhang; Ran Song; Jian Wang; Dong Meng (Engineering Structures, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Medium-chain triglyceride-stabilized docetaxel-loaded HSA nanoparticles effectively inhibited metastatic non-small cell lung cancer - Yunlong Cheng; Xiaoying Pang; Jing Wu; Lingling Zhou; Jinxu Cao; Liuchang Wang; Kang Qian; Peng Yang; Minjun Xu; Dongyu Sheng; Ran Meng; Pengzhen Wang; et al. (Drug Delivery and Translational Research, 2023)

Urbanization reduces soil microbial network complexity and stability in the megacity of Shanghai - Lan Liu; Zhaochen Zhang; Xin Wang; Ran Zhang; Meng Wang; Nina Wurzburger; Junxiang Li; Jian Zhang (Science of The Total Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Clinical and molecular epidemiologic features of enterovirus D68 infection in children with acute lower respiratory tract infection in China - Qi Li; Xiangpeng Chen; Junhong Ai; Lei Li; Changchong Li; Yun Zhu; Ran Wang; Yali Duan; Meng Zhang; Zhengde Xie (Archives of Virology, 2023)

Three new sesquilignans from the stems of Eleutherococcus senticosus and their bioactivities - Yue Zhang; Yi-Ming Zhao; Xiao-Jing Shao; Xue-Hui Wang; Tian-Tian Bei; Yi-Ran Jiang; Wen-Hui Xu; Hyun-Sun Lee; Meng-Xue Xiu; Jian Song; Long Cui (Phytochemistry Letters, 2023)

Natural restoration enhances soil multitrophic network complexity and ecosystem functions in the Loess Plateau - Jia He; Junhong Zhang; Jianyu Wang; Zhenghong Dong; Zexin Meng; Ran Xu; Yongbiao Ji; Yuyu Li; Jun Chen; Xuyang Qi; Xinsheng Wang; Xiuting Li; et al. (CATENA, 2023)

Remote estimation of leaf water concentration in winter wheat under different nitrogen treatments and plant growth stages - Li He; Meng-Ran Liu; Shao-Hua Zhang; Han-Wen Guan; Chen-Yang Wang; Wei Feng; Tian-Cai Guo (Precision Agriculture, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

A compound of paraprobiotic and postbiotic derived from autochthonous microorganisms improved growth performance, epidermal mucus, liver and gut health and gut microbiota of common carp (Cyprinus carpio) - Delong Meng; Qiang Hao; Qingshuang Zhang; Zhe Yu; Shubin Liu; Yalin Yang; Chao Ran; Zhen Zhang; Zhigang Zhou (Aquaculture, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Selenium Deficiency Leads to Reduced Skeletal Muscle Cell Differentiation by Oxidative Stress in Mice - Bo-wen Bao; Zibo Kang; Yu Zhang; Kan Li; Ran Xu; Meng-yao Guo (Biological Trace Element Research, 2023)

Persistent luminescence-activated Janus nanomotors with integration of photodynamic and photothermal cancer therapies - Zhanlin Zhang; Tian Xia; Pan Ran; Junwu Wei; Jie Meng; Guiyuan Zhang; Xiaohong Li (Chemical Engineering Journal, 2023)

Superwettable Surface-Dependent efficiently electrocatalytic water splitting based on their excellent liquid adsorption and gas desorption - Fei Zhang; Ran Zhao; Yiran Wang; Lu Han; Jianmin Gu; Zhimin Niu; Yiming Yuan; Nianrui Qu; Jingxin Meng; Desong Wang (Chemical Engineering Journal, 2023)

Mycotoxin surveillance on wheats in Shandong province, China, reveals non-negligible probabilistic health risk of chronic gastrointestinal diseases posed by deoxynivalenol - Fenghua Li; Xinglan Duan; Liwen Zhang; Dafeng Jiang; Xianqi Zhao; En Meng; Ran Yi; Chang Liu; Yirui Li; Jia-Sheng Wang; Xiulan Zhao; Wei Li; et al. (Environmental Science and Pollution Research, 2022)

Tracking Neural Stem Cells in vivo: Achievements and Limitations - Chun-Ran Xue; Kan Wang; Meng-Ze Zhang; Ze Wang; Ya-Ying Song; Hao-Jun Yu; Yong Hao; Yang-Tai Guan (Stem Cell Reviews and Reports, 2022)

Functional connectivity patterns of the subgenual anterior cingulate cortex in first-episode refractory major depressive disorder - Bochao Cheng; Yajing Meng; Yan Zuo; Yi Guo; Xiuli Wang; Song Wang; Ran Zhang; Wei Deng; Yingkun Guo; Gang Ning (Brain Imaging and Behavior, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

Suitable habitat prediction of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) and its implications for conservation in Baihe Nature Reserve, Sichuan, China - Xin Dong; Yuan-meng-ran Chu; Xiaodong Gu; Qiongyu Huang; Jindong Zhang; Wenke Bai (Environmental Science and Pollution Research, 2019)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Transcriptome profiling analysis of differentially expressed mRNAs and lncRNAs in HepG2 cells treated with peptide 9R-P201 - Wenrong Liu; Ruofan Ding; Yiming Zhang; Canquan Mao; Ran Kang; Junhua Meng; Qingqing Huang; Lili Xiong; Zhiyun Guo (Biotechnology Letters, 2017)

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

Reply to Shaocheng Ji’s discussion on ‘Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process’ by Yang et al. (Contrib. Mineral. Petrol., 2014, 167: 1013) - Jian-Jun Yang; Meng-Xi Huang; Hao-Ran Zhang; Cong Yu (Contributions to Mineralogy and Petrology, 2015)

Role of Liver in Modulating the Release of Inflammatory Cytokines Involved in Lung and Multiple Organ Dysfunction in Severe Acute Pancreatitis - Yilin Wang; Weiyan Liu; Xiqiang Liu; Meng Sheng; Yaofei Pei; Ruoqing Lei; Shengdao Zhang; Ran Tao (Cell Biochemistry and Biophysics, 2015)

Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process - Jian-Jun Yang; Meng-Xi Huang; Qian-Yi Wu; Hao-Ran Zhang (Contributions to Mineralogy and Petrology, 2014)

Nitric oxide is involved in the regulation of trehalose accumulation under heat stress in Pleurotus eryngii var. tuoliensis - Wei-Wei Kong; Chen-Yang Huang; Qiang Chen; Ya-Jie Zou; Meng-Ran Zhao; Jin-Xia Zhang (Biotechnology Letters, 2012)

Functional recombinant human anti-HAV antibody expressed in milk of transgenic mice - Ran Zhang; Man Rao; Chuan Li; Jingyuan Cao; Qinglin Meng; Min Zheng; Meili Wang; Yunping Dai; Mifang Liang; Ning Li (Transgenic Research, 2009)

The genetic mechanism of a translational landslide - Xuan-Mei Fan; Qiang Xu; Zhuo-Yuan Zhang; Dong-si Meng; Ran Tang (Bulletin of Engineering Geology and the Environment, 2009)